Resolving the backbone of the Brassicaceae phylogeny for investigating trait diversity. Issue 3 (12th March 2019) - Nikolov, Lachezar A.; Shushkov, Philip; Nevado, Bruno; Gan, Xiangchao; Al‐Shehbaz, Ihsan A.; Filatov, Dmitry; Bailey, C. Donovan; Tsiantis, Miltos
Summary: The Brassicaceae family comprises c . 4000 species including economically important crops and the model plant Arabidopsis thaliana . Despite their importance, the relationships among major lineages in the family remain unresolved, hampering comparative research. Here, we inferred a Brassicaceae phylogeny using newly generated targeted enrichment sequence data of 1827 exons (> 940 000 bases) representing 63 species, as well as sequenced genome data of 16 species, together representing 50 of the 52 currently recognized Brassicaceae tribes. A third of the samples were derived from herbarium material, facilitating broad taxonomic coverage of the family. Six major clades formed successive sister groups to the rest of Brassicaceae. We also recovered strong support for novel relationships among tribes, and resolved the position of 16 taxa previously not assigned to a tribe. The broad utility of these phylogenetic results is illustrated through a comparative investigation of genome‐wide expression signatures that distinguish simple from complex leaves in Brassicaceae. Our study provides an easily extendable dataset for further advances in Brassicaceae systematics and a timely higher‐level phylogenetic framework for a wide range of comparative studies of multiple traits in an intensively investigated group of plants.